The Use of Flashcard in Teaching English Vocabularies by Young Mothers - Nurnaningsih (Surakarta English and Literature Journal, 2021)
This study aims to determine how to apply flashcards in teaching English vocabulary by young mothers in the Dawis PKK Desa Dua Belasan RT I RW III Jombor Kec. Bendosari Kab Sukoharjo. The problems in this study were examined by qualitative descriptive research because the results of the approach were explained by using words. This research was conducted in the village of Dua belasan Jombor Sukoharjo. Meanwhile, data collection techniques are observation and documentation. The use of flashcards to teach English can be done in three ways. Flashcards in the standard way, namely quickly changing flashcards in front of the children, then flashcards were combined with songs and lastly flashcards were combined with hide and seek games. There are two advantages of a flashcard, it is like a game and it can be combined by singing a song. Apart from that, there are two weaknesses of using the flashcard. Teachers must be creative and must find ways to integrate other media on an ongoing basis. Then, Children did not feel bored in learning English using flashcards.